(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article aimed to compare the solutions for cost statement preparation em-ployed by a hospital operating as an independent public health care institution and ahospital operating as a limited liability company.For the purposes of collecting data for the study, a questionnaire survey was administered to chief accountants of hospitals in West Pomeranian Voivodeship.The results indicate that the hospitals covered under the study employ different solutions for cost statement preparation, particularly with regard to the calculation of the unit cost, which makes it difficult to compare the infor-mation of costs with respect to the health services they provide.